An Evaluation of the Activated Partial Thromboplastin Time Waveform. (July 2018) - Matsumoto, Takeshi; Wada, Hideo; Fujimoto, Naoki; Toyoda, Junki; Abe, Yasunori; Ohishi, Kohshi; Yamashita, Yoshiki; Ikejiri, Makoto; Hasegawa, Kei; Suzuki, Kei; Imai, Hiroshi; Nakatani, Kaname; et al.
The activated partial thromboplastin time (APTT) waveform includes several parameters that are related to various underlying diseases. The APTT waveform was examined in various diseases. Regarding the pattern of APTT waveform, a biphasic pattern of the first or second derivative curve (DC) was observed in patients with hemophilia and patients positive for antiphospholipid (aPL) antibodies or coagulation factor VIII (FVIII) inhibitors. The time of the first and second DC and fibrin formation at 1/2 height were prolonged in patients with hemophilia, patients with inhibitors, patients positive for aPL, patients treated with anti-Xa agents, and patients with disseminated intravascular coagulation (DIC). These values all tended to decrease in pregnant women (at 28-36 weeks' gestation). The height of the second derivative peak 1 was significantly lower in patients with hemophilia, patients with FVIII inhibitors, patients positive for aPL, patients treated with anti-Xa agents, and patients with DIC; these values tended to be significantly higher in pregnant women. The height of the first DC was significantly lower in patients who were positive for FVIII inhibitors and was significantly higher in patients treated with anti-Xa agents and pregnant women. The height of the first and second DC was useful for the analysis of hemophilia, FVIII inhibitor, and aPL.